(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Firm performance comes as a result of the contribution of different factors among which is the shareholding structure of such firm. This paper investigates the impact of shareholding structure on the performance of listed conglomerate firm in Nigeria. The sample of the study is all the 6 firms representing the whole population of the study. The study adopted ex-pot facto research design; using secondary data extracted from the annual report and account of the sampled firms within the period of 2008/2013. Panel multiple linear regression technique was used as a technique of data analysis. The study found that managerial ownership and independent director’s ownership has a negative but strong and significant impact on the performance of listed conglomerate firms in Nigeria, whereas institutional and ownership concentration were found to have a positive, strong and significant impact on the performance of listed conglomerate firm in Nigeria. On the other hand foreign ownership was found to have no significant impact on the performance. It is therefore recommended that management of firms in the conglomerate sub-sector should advice and lobby institutions and individual block holders to subscribe more of their shares as it increase the firm performance, while managers should be discourage by the board to hold a substantial unit of shares by instituting a policy that will restrict the number of their holdings to avoid decrease in performance.